PENGARUH PEMBERIAN JUS MENTIMUN KOMBINASI SEMANGKA TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI WILAYAH PUSKESMAS REJOSARI PEKANBARU - Sofiantii, Putri; Ramadhani, Dyah Wulan (Ensiklopedia of Journal, 2025)
Hypertension is a condition of high blood pressure that is often referred to as a "silent killer" because it does not always show symptoms but can cause serious complications such as stroke and heart disease. The purpose of this study was to determine the effect of giving cucumber juice combined with watermelon on reducing blood pressure in hypertensive patients in the Rejosari Pekanbaru Health Center area. The research method used is quantitative research using the Quasi Experiment method through the Two Group Pre-test Post-test research design. This research was conducted on January 16-27, 2025. The population in this study were 103 Hypertension patients. Sample selection used the probability sampling technique with the propational random sampling technique with a sample size of 50 respondents. Data collection used observation sheets. Data analysis using SPSS which was analyzed univariately and bivariately with the Wilcoxon Non-Parametric test. The results of the study in the intervention group obtained systolic blood pressure values with a p value of 0.000 (<0.05), while diastolic blood pressure obtained a p value of 0.001 (<0.05) which means there is a change in blood pressure. The results of the study in the control group obtained systolic blood pressure valueswith a p value of 0.170 (>0.05), while diastolic blood pressure obtained a p value of 0.101 (>0.05) which means there is no change in blood pressure. So it can be concluded that there is a significant difference after being given treatment. Suggestions for further researchers are expected that hypertension sufferers can apply cucumber juice combined with watermelon to lower blood pressure. Keywords: Hypertension, Cucumber Juice, Watermelon Juice